Corrosion Inhibition and the Synergistic Effect of Three Different Inhibitors on Copper Surface. (1st May 2022) - Wu, Tongxi; Gao, Baohong; Zheng, Qingping; Liu, Shitong; Wang, Jing
Abstract : Copper(Cu) has been an interconnect material widely used in giant-large scale integrated circuits (GLSI). Corrosion inhibitor is a key factor to ensure global planarization of Cu in the CMP slurry. In this paper, three selected inhibitors BTA(Benzotriazole), TAZ(1, 2, 4-triazole), and MBO( 2-Benzoxazolethione) were investigated inhibition behaviors and synergy on the Cu surface. The results show that they are all effective Cu inhibitors in alkaline solutions. MBO loses its ability in H2 O2, but BTA and TAZ do not. The calculated synergistic parameters of BTA/TAZ is 0.1763, XPS and UV–Via experiments show that the antagonism between them is caused by two competitive reactions due to the similar adsorption mechanism: one is the competition for the adsorption site on the surface, and the other is the competition of copper ions that affects the formation of Cu(I)-BTA. The calculated synergistic parameter of BTA/MBO is 1.7763, the synergy between them is obvious.